Impact of european directive 2002/44/ec on the risk of developing hand-arm vibration syndrome in great britain - Brereton, Paul (Canadian Acoustics, 2011)
Trends in risk from hand-arm vibration (HAV) since 1994 are reported, based on work for the Health & Safety Executive (HSE) with employees, employers, suppliers, and their vibration advisers. Work has included inspection of workplaces, investigation of reportable cases of hand-arm vibration syndrome (HAVS), and activities to raise awareness of risks from HAV and their control. A HSE sponsored study in the mid 1990s found that about 5 million people were exposed to HAV at work in Great Britain. Industrial Injuries Disablement Benefit (IIDB) is paid for disabling cases of HAVS in specified industries and for Carpal Tunnel Syndrome (CTS) associated with exposure to vibration. Re-negotiation of product specifications to avoid time-consuming re-work has reduced HAV exposure for the manufacturer and cost for the customer. Where use of powered hand-tools has continued, it has often been possible to re-equip with lower vibration models.